Labour Market Reforms and Economic Growth. The European Experience in the Nineties - Karl Aiginger (Austrian Institute of Economic Research (WIFO), 2004)
Inflexible labour markets combined with high welfare costs are often thought to be the main cause of low growth in Europe. This paper uses OECD data to assess the relative impact of regulation on differences in economic performance across countries since 1990. The impact of regulation is compared first to that of macroeconomic policies such as fiscal policy, monetary policy and macroeconomic cost management. Secondly it is compared to that of policies boosting investment into long run growth, such as research, education and the diffusion of technology. The main result is that while economic performance is related to regulation, the connection to regulatory change in the nineties is less easy to demonstrate. The impact of macroeconomic policy is important insofar as the US applied more growthoriented fiscal and monetary policies, and some European countries succeeded - in the wake of a severe crisis in competitiveness - in bringing private and public costs in line with productivity and tax revenues. Finally, boosting investment into future growth by encouraging research, education and technology diffusion seem to be at least as important as an agenda focussing on labour market flexibility. Differences in the dynamics of these "drivers of long run growth" are consistent with the differences in growth performance between the US and Europe, as well as between individual European countries.
Keywords: E60; O11; O40; 330; Labour market reforms; market regulation; economic growth; transatlantic differences; Arbeitsmarktflexibilität; Wirkungsanalyse; Wirtschaftswachstum; Vergleich; OECD-Staaten